2006
DOI: 10.1111/j.1469-7998.2006.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Density, habitat use and activity patterns of ocelots (Leopardus pardalis) in the Atlantic Forest of Misiones, Argentina

Abstract: Camera-trap surveys were carried out at two different sites within the Atlantic Forest of Misiones province, Argentina, to study the density, habitat use and activity patterns of ocelots. At Urugua-´ı Provincial Park, 17 different individuals were captured (nine females, six males, two of unknown sex) during a 3-monthlong survey (34 camera stations, 1409 trap days). At Iguazu´National Park, 34 different individuals were trapped (20 adult females, nine adult males, two subadult females and three of unknown sex)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
205
2
34

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(265 citation statements)
references
References 29 publications
(83 reference statements)
24
205
2
34
Order By: Relevance
“…The mostly nocturnal activity pattern has also been reported for crab-eating foxes in the Chaco-Chiquitano Transitional Forest of Bolivia (Maffei et al, 2002), in northeastern Argentina (Di Bitetti et al, 2009) and in southeastern Brazil (Vieira & Port, 2007). Ocelots were predominantly nocturnal in our study area, as also reported for the Bosque Chiquitano of Bolivia (Maffei et al, 2002), the Bolivian Amazon (Gómez et al, 2005), the Atlantic Forest of Argentina (Di Bitetti et al, 2006), and the Peruvian Amazon (Kolowski & Alonso, 2010). This nocturnal behaviour of ocelot may reflect the activity of their favourite small prey (Bianchi et al, 2014), which also tends to be nocturnal (Emmons, 1987).…”
Section: Resultssupporting
confidence: 67%
“…The mostly nocturnal activity pattern has also been reported for crab-eating foxes in the Chaco-Chiquitano Transitional Forest of Bolivia (Maffei et al, 2002), in northeastern Argentina (Di Bitetti et al, 2009) and in southeastern Brazil (Vieira & Port, 2007). Ocelots were predominantly nocturnal in our study area, as also reported for the Bosque Chiquitano of Bolivia (Maffei et al, 2002), the Bolivian Amazon (Gómez et al, 2005), the Atlantic Forest of Argentina (Di Bitetti et al, 2006), and the Peruvian Amazon (Kolowski & Alonso, 2010). This nocturnal behaviour of ocelot may reflect the activity of their favourite small prey (Bianchi et al, 2014), which also tends to be nocturnal (Emmons, 1987).…”
Section: Resultssupporting
confidence: 67%
“…Lo que indica que en total se muestreo una área de 81 km 2 que incluye a la REE (Figura 1). Cada una de las celdas fue de igual tamaño y no más grande que el área de actividad de un ocelote hembra adulta que varía entre 0.7 y 9.6 km 2 (Di Bitetti et al 2006;Sunquist y Sunquist 2002). En cada celda se colocaron tres estaciones de foto trampeo (dos sencillas y una doble), lo que da un total de cuatro cámaras trampa por celda (Figura 1).…”
Section: Diseño De Muestreounclassified
“…En relación al periodo de actividad, se reporta que pueden estar activos durante todo el día, con una mayor actividad por las noches (Di Bitetti et al 2006;Maffei et al 2005, Pérez-Irineo y Santos-Moreno 2014), además de que, su actividad también depende de la actividad de sus presas potenciales (e. g., roedores, reptiles y pequeños mamíferos y aves; Murray y Gardner 1997). Nuestros registros de foto captura sugieren que los ocelotes presentan un periodo de actividad tanto de día como de noche, pero que son preferentemente nocturnos.…”
Section: Individuounclassified
“…Además, a partir de las fotografías es posible registrar especies crípticas, que se mueven largas distancias o que están en bajas densidades (Srbek-Araujo & García 2005, Monroy-Vilchis et al 2009). Sus ventajas incluyen la precisión en la identificación a nivel específico y frecuentemente individual, una eficiencia de detección similar en animales diurnos y nocturnos y la confirmación de especies cuyas huellas no se diferencian , Trolle & Kéry 2003, Wallace et al 2003, Karanth et al 2004, Maffei et al 2004, Di Bitetti et al 2006, Soisalo & Cavalcanti 2006, Dillon & Kelly 2008, Maffei & Noss 2008.…”
unclassified
“…Las cámaras son útiles para evaluar patrones de actividad , Rumiz et al 2002, Pinto de Sá Alves & Andriolo 2005, Monroy-Vilchis et al 2009) y uso de hábitat (Bowkett et al 2007), así como para realizar estimaciones de densidad (Trolle & Kéry 2003, Karanth et al 2004, Maffei et al 2004, Di Bitetti et al 2006, Soisalo & Cavalcanti 2006, Dillon & Kelly 2008, Maffei & Noss 2008, Trolle 2008. La frecuencia de captura ha sido utilizada como un índice de abundancia relativa (IAR) evidenciando su correlación con las densidades absolutas, además de su relativa facilidad de aplicación , O'Brien et al 2003, Silveira et al 2003, De Almeida et al 2004, Yasuda 2004, Kelly 2008, Monroy-Vilchis et al 2009, Rovero & Marshall 2009).…”
unclassified